2014
DOI: 10.3109/02699052.2014.920522
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in disorders of consciousness: Focus on the diagnosis

Abstract: More neuroimaging research is needed before clinical implementation to reach the single-subject diagnosis level, as well as to address the sensitivity and specificity of each technique, whether single or combined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 117 publications
(125 reference statements)
1
101
0
4
Order By: Relevance
“…The present study therefore hypothesized that fLiS should be kept as a separate nomenclature for this state and as one member of the LiS sequence. To be consistent with the classification of other MCS (MCS-and MCS+), Gosseries et al (13) proposed MCS* as an indicator of VS with covert awareness. However, para-clinical tests indicate no functional communication and no between-network anti-correlation in patients with fMCS (12).…”
Section: Controversy Over the Concept Of Consciousnessmentioning
confidence: 98%
“…The present study therefore hypothesized that fLiS should be kept as a separate nomenclature for this state and as one member of the LiS sequence. To be consistent with the classification of other MCS (MCS-and MCS+), Gosseries et al (13) proposed MCS* as an indicator of VS with covert awareness. However, para-clinical tests indicate no functional communication and no between-network anti-correlation in patients with fMCS (12).…”
Section: Controversy Over the Concept Of Consciousnessmentioning
confidence: 98%
“…De plus, l'implémentation de cette échelle doit se faire avec des outils appropriés. Par exemple, la poursuite visuelle sera significativement plus souvent observée si elle est testée avec un miroir et le patient localisera davantage un son s'il est appelé par son prénom [21][22][23][24]. Une récente étude a également montré que certains items étaient plus fréquemment observés chez les patients en ECM : la réponse à la commande, la poursuite visuelle, la fixation, les comportements moteurs automatiques et la localisation à la douleur.…”
Section: éChelles Comportementalesunclassified
“…Ainsi, jusqu'à 30 % des patients ne montrent cliniquement aucun signe de conscience, mais présentent une activité cérébrale compatible avec une conscience résiduelle [13]. Ces patients sont considérés en ECM non comportemental [23]. À l'inverse, si malgré les diffé-rents examens aucune activité cérébrale compatible avec une conscience résiduelle n'est détectée, cela exclut la possibilité d'un ECM non comportemental et plaide en faveur d'un ENR ou d'un coma (en fonction de si le patient ouvre les yeux ou non, respectivement).…”
Section: Neuro-imagerieunclassified
See 1 more Smart Citation
“…Thus, patients who demonstrate covert awareness using mental imagery, or other neural responses, still satisfy the behavioural definition of the vegetative state. For this reason, it has been suggested that functional neuroimaging data be incorporated into the diagnostic criteria for vegetative state, in concert with behavioural diagnostic tools (Coleman et al 2009;Laureys and Schiff 2012;Gosseries et al 2014;Peterson et al 2015). However, these techniques remain investigational in this patient population, and changes to the diagnostic criteria of the vegetative state have yet to gain wide acceptance.…”
mentioning
confidence: 99%